Fracture risk of young adults receiving proton‐pump inhibitors and H2‐receptor antagonists. Issue 5 (27th March 2019) - Fedida, Benjamin; Schermann, Haggai; Ankory, Ran; Rotman, Dani; Shichman, Ittai; Yoffe, Vicky; Shlaifer, Amir; Luger, Elhanan
Summary: Introduction: Proton‐pump inhibitors (PPI) and histamine (type 2) receptor antagonists (H2RA) have the potential to interfere with calcium metabolism. Several authors have evaluated the effect of these medications on fracture incidence in older adults. A recent large epidemiologic study demonstrated a higher risk of fractures in young adults receiving PPI. Aim: To evaluate the effect of PPI and H2RA use on fracture incidence in a large retrospective cohort of military recruits representative of general population of young adults. Methods: A retrospective cohort of 254 265 male and 234 670 female non‐combat military conscripts ages 18‐25. Subjects were divided into three groups by PPI use (no PPI use, 1‐100 tablets and more than 100 tablets) and two groups by H2RA use (no H2RA use, any H2RA use). Multivariate logistic regression was used to adjust fracture risk for age, BMI, education level, socio‐economic level, ethnic origin, occupation and duration of follow‐up in months. Main outcome measures: At least one fracture during the study period. Results: Use of PPI and H2RA was not associated with an increased risk of fractures. In men, the predictors of an increased fracture risk were higher BMI (OR = 1.007, P < 0.001), origin from a developing country (OR = 1.15, P < 0.001) and service as a driver (OR = 1.11, P < 0.001). Higher education, higher socioeconomic status and service as an officer or as an administrative worker had a protective effect on fracture incidence. In women, fractures were associated with higher BMI (OR = 1.035, P < 0.001). Origin from a developed country, as well as service as an officer or an administrative worker was associated with lower fracture risk. Conclusions: There was no association between the use of PPI or H2‐antagonists and fracture incidence in this retrospective cohort of healthy young military recruits.